Trends in insecticide usage among bitter gourd farmers of central Kerala: An investigative study - Venugopal, Vineetha; Chellappan, Mani; Pathrose, Berin (Journal of Tropical Agriculture, 2024)
The wide usage of insecticides by farmers in Kerala to improve the quality and production of crops has become a prevailing practice. The urgency to safeguard their crops from detrimental infestations has driven farmers to rely heavily on these chemical interventions. The findings of a survey conducted among 120 farmers from four districts of central Kerala to know the insecticide usage pattern and the preferred insecticides of bitter gourd farmers revealed a significant reliance on insecticides, and farmers often resort to the liberal application of insecticides to safeguard their crops and ensure high yields. The results indicated that the farmers relied heavily on insecticides to control the insect pests of cucurbits. Farmers undertook an average of 5.00-7.00 sprays per crop season at intervals between12.00 and15.00 days, with the least interval being in Palakkad and Thrissur districts. Farmers in Ernakulam district carried out the least number of sprays. Also the results underscore the urgent need for interventions to promote sustainable and responsible insecticide use by implementing educational initiatives, disseminating information on alternative pest management strategies, and fostering a culture of environmental stewardship. The most preferred insecticides among the bitter gourd farmers were chlorantraniliprole, thiamethoxam, malathion, flubendiamide, and dimethoate.